Peningkatan Kapasitas dan Kualitas Produksi Usaha Rengginang Berbasis Green economy di Desa Setro, Kecamatan Menganti, Kabupaten Gresik - Nur Irmayanti; Wahyu Nugroho; Muzakki Muzakki (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2025)
This community service program partnered with Bu Sayem, a rengginang (traditional rice cracker) entrepreneur in Setro Village, Menganti Sub-district, Gresik Regency, which has significant local economic potential through rengginang production. The program was conducted from July to October 2024, aiming to enhance the production capacity and quality of rengginang through the application of appropriate technology (TTG) and a green economy approach. Setro Village faces challenges such as low production capacity, suboptimal product quality, and environmentally unfriendly production methods. The program's interventions included the use of modern stainless-steel molding machines and ovens, which increased production capacity by up to 30%. Additionally, training and mentoring sessions improved the entrepreneur’s understanding of food safety standards and the importance of digital marketing to expand market reach. The program's outcomes demonstrate that this intervention model effectively supports local economic sustainability, fosters environmentally friendly industries, and enhances product competitiveness. It is expected that this approach can be adopted by other MSMEs in the region to support community-based economic development.